Formate as an Intermediate in the Bovine Rumen Fermentation - Hungate, R. E. (1970)
An average of 11 (range, 2 to 47) μmoles of formate per g per hr was produced and used in whole bovine rumen contents incubated in vitro, as calculated from the product of the specific turnover rate constant, k, times the concentration of intercellular formate. The latter varied between 5 and 26 (average, 12) nmoles/g. The concentration of formate in the total rumen contents was as much as 1,000 times greater, presumably owing to formate within the microbial cells. The concentration of formate in rumen contents minus most of the plant solids was varied, and from the rates of methanogenesis the Michaelis constant, K(m), for formate conversion to CH(4) was estimated at 30 nmoles/g. Also, the dissolved H(2) was measured in relation to methane production, and a K(m) of 1 nmole/g was obtained. A pure culture of Methanobacterium ruminantium showed a K(m) of 1 nmole of H(2)/g, but the K(m) for formate was much higher than the 30 nmoles for the rumen contents. It is concluded that nonmethanogenic microbes metabolize intercellular formate in the rumen. CO(2) and H(2) are the principal substrates for rumen methanogenesis. Eighteen per cent of the rumen methane is derived from formate, as calculated from the intercellular concentration of hydrogen and formate in the rumen, the Michaelis constants for conversion of these substrates by rumen liquid, and the relative capacities of whole rumen contents to ferment these substrates.